2021
DOI: 10.18421/tem101-42
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Motivation in the 21st Century in Terms of Pull and Push Factors

Abstract: The socio-economic importance of entrepreneurship in the 21st century in relation to economic growth has become undisputable on local and global level both in terms of macroeconomic indicators, as well as the micro environment. Despite the above, this field still offers questions to be addressed, and these are related to the entrepreneurs themselves, entrepreneurial behaviour, motivation to start business, but also the entrepreneurial environment that encourages or hampers their activities or attitudes. Entrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Among these, the manager can influence the business activities, decision making, performance, and value of the firm due to the motivation of the start-up of the manager. Gódány et al [17] suggested the push factors as having a decisive effect on the turnover of managers. Since the manager's remuneration can be a representative push factor, if the managerial compensation is the decisive motive for starting a business and the manager's compensation is low, job turnover and negligence can occur.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Among these, the manager can influence the business activities, decision making, performance, and value of the firm due to the motivation of the start-up of the manager. Gódány et al [17] suggested the push factors as having a decisive effect on the turnover of managers. Since the manager's remuneration can be a representative push factor, if the managerial compensation is the decisive motive for starting a business and the manager's compensation is low, job turnover and negligence can occur.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…gold during the so-called gold standard), but its concept is completely different in that it is not linked to another commodity Buleca 2012, Orgonáš et al 2020). Enforcement here takes the form of a legal norm by which a public authority establishes and implements a specific system of money and systematically regulates with its legal system the individual aspects of its circulation and protection, thus enshrining the currency as a legal form of money (Godany et al 2021, Repnikova et al 2019, Wulandari et al 2019. The establishment of a currency is always a legal act and the currency is one of the attributes of state sovereignty (Prokopenko and Kornatowski 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although the pull motivation of start-ups is extremely private factors, such as wanting to run one's own business, be recognized by others, etc. [5], the aggregate of these motivations could make the economies of many countries more innovative and dynamic. However, business creation alone is not sufficient to grow the national economy and increase employment.…”
Section: Introductionmentioning
confidence: 99%